Seasonal biofilm formation on floating microplastics in coastal waters of intensified marinculture area. (October 2021) - Dong, Xuri; Zhu, Lixin; Jiang, Peilin; Wang, Xiaohui; Liu, Kai; Li, Changjun; Li, Daoji
Abstract: The environmental pollution caused by microplastics has received increasing attention recently. In this paper, we present the results of research into the bacterium attached to microplastics in four coastal mariculture zones in southeast China during winter and summer. Polyethene and polypropylene are the main microplastics in the surface water of mariculture area. The differences between the bacteria species composition found on the surface of microplastics in winter and summer were less than that found in the planktonic bacteria, indicating that biofilms protect the bacterium that live inside. Potentially pathogenic Vibrio and Pseudomonas spp. were more abundant in samples from ShanTou and QuanZhou during the summer. Bacteria related to the degradation of microplastics were found extensively on the surface of microplastics at all of the sampling sites. More attention should be paid to the risks resulting from the accumulation of harmful bacteria on microplastic surfaces during the summer. Highlights: Bacteria were examined in the surface biofilms of microplastics in the aquacultural waters of SE China. Microplastic surface biofilm bacteria mainly originate from the aquatic environment. Biofilms on the surface of microplastics provide protection for the bacterium that live in them. Pathogenic bacteria and plastic-decomposing bacteria are widely distributed on microplastics in the study area.